Pre-service Teachers’ Preparedness for In-service Science Teaching in Primary Education – A Case Study in Croatia - Erceg, Nataša; Alajbeg, Anna (Sustainable business and society in emerging economies, 2024)
An experimental science curriculum for primary school was introduced in Croatia for the 1st time in the 2023/24 school year. This is taking place against the backdrop of a shortage of teachers from various science subjects, especially physics. They are increasingly being replaced by non-professional teachers, often those with a Master of Primary Education, which gives access to the profession of primary junior grade teacher. In this study, the subject matter knowledge (SMK) in science of 44 pre-service teachers aiming for the above-mentioned degree is examined using the SMK test. The test contains 40 trends in international mathematics and science study (TIMSS) items from the 4th-grade science content domain Physical Science and allowed us to compare the achievement of our respondents with the achievement of pupils who participated in the TIMSS assessments. The results show that the percentage correctness of the pre-service teachers on the SMK test was statistically significantly higher than that of the 4th-grade pupils. However, the correlation coefficients showed that the pre-service teachers had greater difficulties with the items with which the pupils had greater difficulties, and vice versa. This applies in particular to the items on forces and motion and to the items from the cognitive domain of reasoning. The reason for the unsatisfactory science SMK of our respondents could be the incompatibility of the university science curriculum with the demands placed on pupils in the relevant school subjects and International science assessments such as TIMSS. The results of this study confirm and extend the contribution of existing research and should serve as a basis for subsequent research as well as for the design of a further course of science education reform in Croatia and in the countries of the region.